2020
DOI: 10.1177/2382120520959691
|View full text |Cite
|
Sign up to set email alerts
|

Wikipedia: A Medical Student Educational Project to Edit Wikipedia in Preparation for Practicing Evidence-Based Pain Medicine

Abstract: Objective: Wikipedia is commonly used to acquire information about various medical conditions such as chronic pain. Ideally, better online pain management content could reduce the burden of opioid use disorders. Our goal was to improve the quality of the content available on Wikipedia to make it more accurate and applicable to medical students and the general public while training medical students to practice evidence-based medicine and critically assess their sources of information. Methods: An elective class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The diversity and breadth of the examples we summarize demonstrate an emerging “ally-ship” between health professions education and Wikipedia. Teaching students to contribute to Wikipedia provides excellent opportunities for students to develop evidence-based medicine skills [ 24 26 ]. Notably, there are a myriad of ways to deliver these courses to the audience, including live sessions, videos, and online interactive platforms, any/all of which can be delivered both in person and remotely [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diversity and breadth of the examples we summarize demonstrate an emerging “ally-ship” between health professions education and Wikipedia. Teaching students to contribute to Wikipedia provides excellent opportunities for students to develop evidence-based medicine skills [ 24 26 ]. Notably, there are a myriad of ways to deliver these courses to the audience, including live sessions, videos, and online interactive platforms, any/all of which can be delivered both in person and remotely [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior use of Wikipedia editing with first-year medical students has shown that it can improve their confidence in locating knowledge gaps, literature searching, group work, and selecting reliable sources [ 10 ]. Subsequent studies with third- and fourth-year medical students, and allied health students, cite an increase in students' self-perceived ability to practice evidence-based medicine and satisfaction with “giving back” to Wikipedia [ 7 , 9 ]. As such, Wikipedia editing serves as a vehicle for social responsibility by allowing students to contribute to, improve, and expand health information read by millions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we define lifelong learning in the context of information literacy skills, specifically, their ability to search and retrieve biomedical information, critically appraise the information they find, and their ability to apply it to patients and populations (in this case, to readers of Wikipedia) [ 19 ]. Most studies on Wikipedia in the classroom have been concentrated in fields outside of medicine [ 3 – 6 ], other sciences or allied health [ 11 13 , 20 , 21 ], or with more advanced third- and fourth-year medical students [ 7 , 9 ]. Furthermore, most studies investigating information literacy outcomes through Wikipedia editing assignments are concentrated in fields outside of medicine [ 6 , 12 , 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 The first reported use of Wikipedia in 2012 was a neuroscience course in which students edited Wikipedia as a course assignment. 11 Later, Azzam et al 13 described the first for-credit medical course fully dedicated to editing and writing medical articles on Wikipedia. Since then, other health professions have reported integrating Wikipedia into their curriculum, including courses in pain management, 13 pharmacy, 14 nursing, 15 and evidence-based medicine.…”
Section: Introductionmentioning
confidence: 99%
“…11 Later, Azzam et al 13 described the first for-credit medical course fully dedicated to editing and writing medical articles on Wikipedia. Since then, other health professions have reported integrating Wikipedia into their curriculum, including courses in pain management, 13 pharmacy, 14 nursing, 15 and evidence-based medicine. 16 Despite these offerings, tensions still exist over Wikipedia as a trustworthy information source and whether the academic community should promote its use in their classrooms, with some students and instructors relegated to using Wikipedia as a "guilty secret".…”
Section: Introductionmentioning
confidence: 99%